How Consistent Are Challenge and Threat Evaluations? A Generalizability Analysis - Moore, Lee J.; Freeman, Paul; Hase, Adrian; Solomon-Moore, Emma; Arnold, Rachel (Frontiers in Psychology, 2019)
Viewing stressful situations as more of a challenge than a threat (i.e., coping resources match or exceed situational demands) has been associated with better performance and long-term health. However, to date, little research has examined if individuals have tendencies to evaluate all stressful situations as more of a challenge or threat. Thus, this study used generalizability analyses to investigate the consistency (or variability) of challenge and threat evaluations across potentially stressful situations. 1813 roller derby players (89.0% female; Mage = 33 years, SD = 7) read nine stressful vignettes (e.g., injury, non-selection, family illness), before completing self-report items assessing challenge and threat evaluations. Generalizability analyses revealed that the Athlete x Stressor interaction accounted for the greatest amount of variance in challenge and threat evaluations (51.9%), suggesting that athletes had idiosyncrasies in their tendency to view particular stressors as more of a challenge or threat. The Athlete (15.4%) and Stressor (21.9%) components also accounted for a significant amount of variance. While the Athlete component suggested some consistency in challenge and threat evaluations, and that differences existed between athletes in whether they tended to view stressors as more of a challenge or threat, the Stressor component indicated some agreement among the athletes in their tendency to view some stressors as more of a challenge or threat than others. The findings offer direct support for transactional stress theories, and have important implications for practitioners developing stress management interventions.